الصعوبات الصوتية لدى الجاويين المبتدئين في تعلم الللغة العربية وطرق علاجها - Wahid Abdurrohman; Arif Taufikurrahman (Rayah Al-Islam, 2019)
The purpose of this research is to know the acoustic difficulties of Javanese beginner students in learning Arabic language and it’s resolved methods. In this research the writer used the analytical descriptive method, where the writer explained the sounds of Arabic and Javanese language then described the acoustic difficulties of the Javanese people in learning Arabic and how to resolve it. The results from this research stated the acoustic difficulties for the Javanese are divided into two, difficulties related to the Arabic vocal sounds which are difficulties in telling apart the long vocals and short vocals, and acoustic difficulties that are related to consonant sounds found in the 17 phonemes in Arabic language, which are the sounds of the letter ب، ج، ت، د، ر، ث، ح، خ، ذ، ش، ص، ظ، ط، ض، ع، غ، ق . Ways to resolve this problem can be done in many different ways. One of them is using the three methods of sound exercises that are sound identification, sound distinguishing, and abstract sound identification (identifying sounds from sentences), and also by language games, by adjusting our self in speaking and listening to Arabic Language that is correct, by tahsin Al Quran with a professional supervisor, and by good Arabic songs.